New Venture Opportunity Cost of Capital and Financial Contracting - Frank Kerins; Janet K. Smith; Richard L. Smith (Claremont McKenna College, Department of Economics, 2000)
Investments in new ventures involve financial contracts between an entrepreneur and outside investors. Investors, such as venture capital firms, represent well-diversified investors. In contrast, the entrepreneur must commit a substantial fraction of human and financial capital to the venture. Consequently, the entrepreneur's required rate of return depends on total risk, in the context of the entrepreneur's other assets. In this paper, we use the Capital Asset Pricing Model as an approximation of the asset pricing model used by well-diversified investors. Accordingly, the entrepreneur faces the risk-return tradeoff of the CAPM as the opportunity cost of holding an under-diversified portfolio that includes investment in the venture. We model the required rate of return of the entrepreneur, assuming investment in the venture is one of two assets in the portfolio and that the other is the market portfolio. We explore opportunities for value creation when the parties to a financial contract have different costs of bearing risk. We also present empirical data on factors relevant to new venture cost of capital estimation.
Keywords: 330